@Ferguson: : Still here in the afterlives of Black death, defiance, and joy An American Ethnologist forum, edited by Shanti Parikh and Jong Bum Kwon. (17th September 2020) - Unknown
ABSTRACT: On August 9, 2014, a police officer murdered unarmed Black teenager Michael Brown in the St. Louis suburb of Ferguson. Brown's murder, and the globally watched uprising it ignited, incited a variety of cultural‐political productions and affects, some of which are collected in this forum as a collage of art, photography, personal essays, poetry, and anthropological analyses. This forum's rationale follows that of Mirror Casket, a work of public art created by local artivists. Mirror Casket memorializes Brown and challenges viewers to see their own part in perpetuating premature Black death—and their obligation to end it. Constructed with broken pieces of mirrored glass, Mirror Casket embodies a fractured region, historically created through Black death and sociogeographic containment, and its polarized responses to the uprising—on the one hand, militarized police and uninhibited anti‐Black racism, and on the other, Black mourning and emerging young leadership, and cross‐racial protests and struggles with fear, anxiety, rage, and despair. Mirror Casket, like the pieces in this forum, also demonstrates the creative persistence and generativity that persists in the afterlife of Brown's death. Inspired by its coproducers, "@Ferguson" aims not to offer conclusions but to explore the aesthetic, affective, and political provocations of what became the template for 21st‐century Black liberation. Moreover, it challenges anthropology's long‐standing attachments to "disciplined" white institutional and cultural traditions. [ race, social movement, protest art, decolonizing methods, necropolitics, biopolitics, urban, police brutality, Blackness, Ferguson ]